2013
DOI: 10.1111/jopr.12101
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Patient Satisfaction Levels with Complete Dentures of Different Occlusions: A Randomized Clinical Trial

Abstract: With the caution of small sample size, the results of this study provide evidence that use of BO can improve food avoidance and physical disability aspects of patient satisfaction with complete dentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 26 publications
1
60
0
1
Order By: Relevance
“…6 In a recent clinical trial, we presented new BO and tested it for the fabrication of CCDs. 16 This study showed that while there were no significant differences between BO and LO, both these occlusal schemes provided fewer eating problems and physical disabilities. In addition, these occlusal schemes were associated with more comfortable dentures and more diverse diet than FBBO.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…6 In a recent clinical trial, we presented new BO and tested it for the fabrication of CCDs. 16 This study showed that while there were no significant differences between BO and LO, both these occlusal schemes provided fewer eating problems and physical disabilities. In addition, these occlusal schemes were associated with more comfortable dentures and more diverse diet than FBBO.…”
Section: Introductionmentioning
confidence: 64%
“…The checklist included demographic variables, skeletal base classification, 19-item version of OHIP-EDENT questionnaire, 16,19 VAS line for the prosthodontist's attitude towards the quality of CCD and 7…”
Section: Follow-up Evaluationmentioning
confidence: 99%
See 3 more Smart Citations